Protocols for Antioxidant Testing: A Mini Review of Common Assays and Approaches - Halboup, Abdulsalam; Alkubati, Sameer A. (AUIQ Complementary Biological System, 2025)
Antioxidants play a pivotal role in mitigating damage caused by oxidative stress, which is implicated in aging, inflammation, neurodegeneration, and various chronic diseases. With the growing interest in natural and synthetic antioxidants across nutraceutical, pharmaceutical, and food industries, the need for reliable, reproducible, and standardized testing methods has become increasingly urgent. This mini-review provides a structured overview of the most widely used antioxidant testing protocols, categorized into in vitro chemical-based assays (e.g., DPPH, ABTS, FRAP, metal chelation), cell-based assays (e.g., DCFH-DA for intracellular ROS detection), and in vivo biomarker-based models. Each methods principle, experimental protocol, advantages, and limitations are critically discussed. The review further highlights the importance of assay selection based on mechanistic relevance, distinguishing between primary radical scavenging and secondary antioxidant mechanisms. Finally, it addresses major challenges in assay variability, poor in vitroin vivo correlation, and calls for methodological standardization and integration of emerging biosensing and high-throughput approaches for future advancements.